Life Stories on the Social Image of Disability. An Educational Outlook - Mañas-Olmo, Moisés Antonio; Cortés-González, Pablo; Celada, Beatriz Margarita (Hipatia Press, 2020)
This paper forms part of the results of the ongoing doctoral thesis with the title Resilience and intellectual disability in residential environments using life stories. From a narrative and inclusive biographical approach, we delve deeper into the life history of four people who have been diagnosed with intellectual disability and who live in a residential environment in the city of Malaga (Spain). The field work was carried out using semi-structured and in-depth biographical interviews. The analysis reveals one of the conceptions that is a priority in this paper: the “social image”of disability, structured in three main areas for the purposes of this article: “the image of disability from social culture and identity”, “the image of disability from close contexts”and, lastly, “subversive experiences to the image of disability from inside”. In conclusion, there is a commitment to continue generating another social image of disability based on a more social and inclusive paradigm.
Keywords: Personas con discapacidad intelectual - Situación social; Exclusión social; Intellectual disability; Social image; Education; Social exclusion; Culture